Receptor TRKB y conexina 43 en cáncer de ovario - Garrido P., Maritza; Romero O, Carmen (Revista Hospital Clínico Universidad de Chile, 2013)
Ovarian cancer is one of the most aggressive and poor prognosis cancer, which appears predominantly as Epithelial Ovarian Cancer (EOC). Many studies have been conducted to establish connections between neurotrophin receptors and the development, progression and response of cancer therapy. The tyrosine kinases receptors (TRK) have been considered as important target in several cancers, including EOC. Metastasic process and resistance to cancer therapies have been associated with the TRK neurotrophin receptor B (TRKB), whose main ligand is brain derivated neurotrophic ligand (BDNF). Another important aspect in tumor development is the expression of adhesion molecules such as connexin 43. This protein is present in many tissues included the ovary and cancer cells. When TRK receptors are activated by theirs ligands, connexin 43 is phosphorilated and promotes several processes in tissues, like remodeling gap junctions and cellular permeability. All these features are very important in tumor cells, and probably would be involved in the process of metastasis, tumor growth and arrival of nutrients and therapy drugs to the tumor mass. The aim of this revew is to expose current knowledge about connexin 43 and TRKB receptor in ovarian cancer.